Seeking Theoretical Common Ground: An Integrative Framework of Understanding Accountability for Service Delivery in the Community School in Nepal - Khanal, Kul Prasad (Journal of Management and Development Studies, 2019)
Existing literature provides ample evidence on how people understand accountability in different contexts. However, little attention has been paid on the integration of various theoretical perspectives about understanding accountability for education service delivery. Discussing theoretical premises against the empirical evidence from the community schools of Nepal, this article explores common ground of various theoretical perspectives about understanding school actors' accountability. It provides a framework for understanding accountability by integrating the ancient principle of 'karma-yoga' and modern theoretical ingredients of structure-agency and knowledge-power. The article argues that both ancient and modern streams of theoretical perspectives are not mutually exclusive rather they share a common ground of process-based accountability which is embedded in broader concept of responsibility. Finally, the paper contributes to existing literature of accountability in education arguing that the school head’s agency rather than working structure of the school played a significant role in creating an accountable space between the school head and other actors in the community school.